Safety, Efficacy, and Mechanism of Action of Budesonide in Rhinitis and Rhinosinusitis: A Systematic Review - David W. Kennedy; Lei Cheng; De‐Yun Wang (World Journal of Otorhinolaryngology - Head and Neck Surgery, 2026)
ABSTRACT Objective Budesonide is a corticosteroid with unique pharmacokinetic and pharmacodynamic properties that has been a frontline treatment for patients with allergic rhinitis (AR) and chronic rhinosinusitis (CRS) since the 1990s. As research on budesonide continues to produce new insights, our aim was to synthesize recent investigations and provide up‐to‐date information on safety, clinical, and mechanism of action (MOA) outcomes. Data Sources Searches were restricted to PubMed from 2014/01/01 to 2025/02/26. Clinical investigations in the primary therapeutic area of rhinitis, sinusitis, or rhinosinusitis with adult patients receiving budesonide were included. Review Methods Results were screened, and findings from eligible articles were assessed for safety, efficacy, and/or MOA outcomes. Results Overall, 31 articles were included. CRS was the primary indication in 19 studies and rhinitis in 12 (predominantly AR). Six studies investigated hypothalamic–pituitary–adrenal (HPA) axis suppression, and 2 studies assessed intraocular pressure; budesonide did not adversely affect either outcome, even with long‐term, high‐dose, high‐volume nasal irrigations. Twelve studies of budesonide monotherapy generally showed improved efficacy outcomes. Eight studies of budesonide combination therapies, predominantly in patients with moderate‐to‐severe AR, generally showed improved efficacy versus budesonide monotherapy. MOA data were reported across seven studies, with anti‐inflammatory alterations observed across the nasal mucosa, nasal secretions, nasal polyps, and peripheral blood after budesonide treatment. Conclusions Safety outcomes were favorable across various budesonide delivery systems, including high‐dose, high‐volume nasal irrigations, with no evidence of HPA axis suppression after long‐term budesonide use. Budesonide demonstrated consistent efficacy that was underpinned by MOA data on its potent anti‐inflammatory effects.